2020
DOI: 10.1088/1755-1315/486/1/012085
|View full text |Cite
|
Sign up to set email alerts
|

Carbon stock analysis of some cocoa planting systems in South Sulawesi

Abstract: In an effort to control carbon emissions in the air, steps taken are improving forest vegetation and protecting natural forest vegetation as the biggest absorber of carbon gas emissions. Cocoa as the largest plantation crop in Indonesia is expected to be able to absorb CO2 gas emissions in the air due to its ability to absorb carbon. A carbon analysis study was carried out on cacao plantation to determine the level of carbon uptake in each cropping system in South Sulawesi. Hence, the results of the analysis c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
2
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 3 publications
0
2
0
1
Order By: Relevance
“…According to the study's findings, the cocoa-based agroforestry system with multi strata shelters has a total carbon stock of 124,69 tons.ha -1 (Table 1), which is higher than the monoculture cocoa stock of 91.7 tons.ha -1 . The same study in South Sulawesi's Pinrang region found that monoculture cocoa plantations had a total carbon of 21.51 tons.ha -1 , while multi strata cocoa-based agroforestry had an average of 26.34 tons.ha -1 [45]. According to Asrul [44], the multistrata cocoa agroforestry system has a higher carbon stock of 37.68 ton.ha -1 when compared to the 27.09 ton.ha -1 monoculture cocoa grown in Bantaeng, South Sulawesi.…”
Section: Climate Change Mitigation Roles and Functions Of Cocoa-based Agroforestrymentioning
confidence: 93%
See 1 more Smart Citation
“…According to the study's findings, the cocoa-based agroforestry system with multi strata shelters has a total carbon stock of 124,69 tons.ha -1 (Table 1), which is higher than the monoculture cocoa stock of 91.7 tons.ha -1 . The same study in South Sulawesi's Pinrang region found that monoculture cocoa plantations had a total carbon of 21.51 tons.ha -1 , while multi strata cocoa-based agroforestry had an average of 26.34 tons.ha -1 [45]. According to Asrul [44], the multistrata cocoa agroforestry system has a higher carbon stock of 37.68 ton.ha -1 when compared to the 27.09 ton.ha -1 monoculture cocoa grown in Bantaeng, South Sulawesi.…”
Section: Climate Change Mitigation Roles and Functions Of Cocoa-based Agroforestrymentioning
confidence: 93%
“…A cocoa-based agroforestry system is a cocoa cultivation system that makes use of several trees that serve as shade plants. The cocoa agroforestry system will include multi strata shade plants, allowing for the storage of a large amount of carbon [43][44][45][46]. Faradilla [43] compared the carbon stock that can be stored in cocoa plantations with agroforestry systems to monoculture cocoa plantations in three regions of South Sulawesi.…”
Section: Climate Change Mitigation Roles and Functions Of Cocoa-based Agroforestrymentioning
confidence: 99%
“…Karbon tersimpan dalam bentuk biomassa dalam hutan terkandung dalam bagian tumbuhan yang sudah mati seperti batang, ranting pohon maupun serasah yang jatuh ke permukaan tanah (Eslamdoust & Sohrabi 2018). Pengukuran karbon pada tanaman penting untuk memahami penyerapan karbon pada biomassa dapat menunjukkan jumlah CO2 di atmosfer yang terserap oleh tumbuhan dimana pengukuran karbon yang terdapat dalam organ tumbuhan mati (nekromassa) bisa menunjukkan CO2 yang terikat tidak dilepas ke udara pada proses pembakaran atau evaluasi dekomposisi organik (Mustari et al, 2020) Gas karbon terutama karbon dioksida (CO2) dapat diserap melalui beberapa proses oleh tanaman melalui proses fotosintesis yang disimpan dalam tumbuhan hijau dan dikembalikan ke udara dalam bentuk oksigen (O2) melalui proses respirasi untuk menghasilkan energi (Uthbah et al, 2017).…”
Section: Pendahuluanunclassified
“…Karbon juga terkandung dalam bagian tumbuhan yang sudah mati seperti batang, ranting pohon maupun serasah yang jatuh kepermukaan tanah (Eslamdoust & Sohrabi, 2018). Pengukuran karbon pada organ tanaman hidup (biomassa) dapat menunjukkan jumlah CO 2 di atmosfer yang terserap tanaman, sedangkan pengukuran karbon yang tersimpan dalam organ tumbuhan mati (nekromassa) bisa menunjukkan CO 2 yang tidak dilepaskan ke udara melalui pembakaran (Mustari et al, 2020). Gas karbon diserap oleh tanaman melalui proses fotosintesis yang disimpan dalam organ tanaman dan dikembalikan ke udara dalam bentuk oksigen (O 2 ) melalui proses respirasi (Uthbah et al, 2017).…”
Section: Pendahuluanunclassified